On the Numerical Solution of Differential-Algebraic Equations with Hessenberg Index-3 - Melike Karta; Ercan Çelik (Discrete Dynamics in Nature and Society)
Numerical solution of differential-algebraic equations with Hessenberg index-3 is considered by variational iteration method. We applied this method to two examples, and solutions have been compared with those obtained by exact solutions.